Asystasia intrusa: Cover crop and water balance dynamics in oil palm plantation - SATRIAWAN, HALUS; FUADY, ZAHRUL; ERNAWITA, (The Indian Journal of Agricultural Sciences, 2023)
Cultivation of A. intrusa as cover crops in oil palm plantation plays a role in reducing water deficit as much as 90% on condition of higher water deficit occurred. The present study aimed to examine the roles of A. intrusa as land cover crop on water balance in oil palm plantation in Bireuen Regency, Aceh Province, Indonesia during the year of 2020. The initial soil moisture content during the experiment were measured at various depths and conducted using a sensor connected to multimeter. The hydrological variables observed were included rainfall, interception of oil palm plants, water interception of A. intrusa, A. intrusa evapotranspiration, initial soil water content, soil water content during the experiment at each predetermined soil depth and percolation. This study showed that with A. intrusa as cover crop, positively affected soil water content especially during dry season and on months when rainfall are moderate. A. intrusa as cover crops in oil palm plantation played an important role in affecting water balance by reducing ground water deficit during dry season or months with lower rainfall.